Rocking the Holy See. (Economist, 2012)
The article focuses on Cardinal Tarcisio Bertone, the Cardinal Secretary of State in Vatican City. Information is provided on how the hacker group Anonymous compromised the Vatican's website with the intent of removing Bertone from his position because of alleged corruption. It is noted that Bertone will likely have a large influence on choosing the next Pope.